2012
DOI: 10.1111/j.1464-410x.2012.11261.x
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete thermal ablation stimulates proliferation of residual renal carcinoma cells in a translational murine model

Abstract: CA and RFA result in an increased proliferation and decreased apoptosis of residual renal tumour cells. This hyperproliferation may be caused by stimulatory factors, e.g. hypoxia, HSPs and inflammatory cells, and could facilitate recurrences of renal tumours after thermal ablation. This study highlights the importance of achieving complete tumour destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
2
28
0
1
Order By: Relevance
“…Stimulated growth of surviving tumor cells after incomplete thermal ablation (cryoablation or radiofrequency ablation) was observed earlier in renal tumor cells [22] and after incomplete radiofrequency ablation in liver cells [23]. Increased tumor cell proliferation was seen up to the end of the studies, respectively, 14 and 21 days after ablation, and is possibly caused by tissue damage, increased hypoxia, increased presence of heat-shock proteins, and inflammatory cells directly adjacent to the ablation area [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulated growth of surviving tumor cells after incomplete thermal ablation (cryoablation or radiofrequency ablation) was observed earlier in renal tumor cells [22] and after incomplete radiofrequency ablation in liver cells [23]. Increased tumor cell proliferation was seen up to the end of the studies, respectively, 14 and 21 days after ablation, and is possibly caused by tissue damage, increased hypoxia, increased presence of heat-shock proteins, and inflammatory cells directly adjacent to the ablation area [22].…”
Section: Discussionmentioning
confidence: 99%
“…Increased tumor cell proliferation was seen up to the end of the studies, respectively, 14 and 21 days after ablation, and is possibly caused by tissue damage, increased hypoxia, increased presence of heat-shock proteins, and inflammatory cells directly adjacent to the ablation area [22]. The clinical consequences of this effect remain unclear; in the worst-case scenario, it could facilitate tumor outgrowth; and in the best case scenario, the effect is only a temporary reaction on the cellular damage caused by the ablation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with rapid progression in HCC, there are few reports regarding that in RCC. Kroeze et al (29) reported that incomplete thermal ablation stimulated proliferation of residual RCC cells in a murine model. To the best of our knowledge, only one study has previously demonstrated rapid progression following laparoscopic RFA for T1b RCC (4.5 cm) (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing clinical and experimental evidence that RF ablation may, in fact, also induce tumor initiation, growth, and propagation (1,4,5). Several studies suggest that RF ablation may, under unclear clinical circumstances and owing to poorly characterized mechanisms, stimulate growth in residual incompletely treated and viable tumor surrounding the ablation zone for at least some tumor types (eg, HCC or renal cell carcinoma) (4,6,7).…”
Section: Implications For Patient Carementioning
confidence: 99%